You who came from Korean dramas : influence of Korean dramas on young Singaporean adult viewers’ perception of desired gender images - Lim, Celestia Qianyu (2014)
Since the start of the Korean Wave, Korean dramas have been widely consumed and the presence of the Internet has also contributed to the increase in Korean drama viewers in Singapore. Through qualitative interviews with both female and male young adult Korean drama viewers in Singapore, this study seeks to explore the degree of influence that Korean dramas have on young Singaporean adult viewers’ perception of desired gender images. To do that, this study will investigate if young Singaporean adult viewers blur the boundaries between reality and Korean dramas, making them wish for their future potential partner to possess characteristics of Korean drama protagonists, and inculcate patriarchal values embedded in Korean dramas into their reality.